PANDANGAN MUḤAMMAD SA`ĪD RAMAḌĀN AL-BŪṬI TERHADAP MAṢLAḤAH WASIAT WAJIBAH ANAK ANGKAT - Mahbubi, Mahbubi; Ludfi, Ludfi (Al Hakam : The Indonesian Journal of Islamic Family Law and Gender Issues, 2023)
The Compilation of Islamic Law (KHI) regulates mandatory wills for adopted children and adoptive parents, this is stated in article 209 paragraphs (1) and (2). This rule is relatively new when referring to the implementation of mandatory wills implemented in other Islamic countries. In contemporary jurisprudence studies, obligatory wills are only given to heirs who do not receive an inheritance because they are mahjūb by other heirs. The implementation of mandatory wills in Indonesia is considered to involve the mutual benefit of the child and his adoptive parents. Therefore, the focus of this study is to find the suitability of the concept of obligatory wills in KHI with the concept of mashlahah al-Buthi. The type of research used is library research with content analysis, philosophical-hermeneutic and mashlahah approaches. The data collection technique is in the form of documentation through inventory, classification and data evaluation. The results of this research state that mandatory wills in the KHI are only given to adopted children and adoptive parents. This legal formulation is the result of the ijtihad of Indonesian ulama' which aims for the common good. The concept of mashlahah al-Buthi is mashlahah which tries to take the middle path in accordance with what is intended by Syāri', so that giving obligatory wills to adopted children is a real benefit.